Dunia Rambut: Mengenal Struktur, Tekstur, dan Cara Perawatannya - Husniyah, Aneyra Hasna (Maliki Interdisciplinary Journal, 2025)
Hair is one of the thread-like human organs that grow on the skin. Hair emerges from the epidermis layer although its origin is from the hair follicle which is located deep under the dermis layer of the skin. Hair has many textures ranging from straight, wavy to curly hair. These different types of hair have many factors, one of which is genetic and evolutionary. One of the unique facts about hair is how many strands it has. Straight hair has more strands than wavy and curly hair because each strand of hair grows from a follicle on the scalp, while this follicle determines many aspects of the hair. Also, proper hair care depends on the type and texture of the hair. Mistakes in care can cause damage to the hair.